1974
DOI: 10.1007/bf03006016
|View full text |Cite
|
Sign up to set email alerts
|

General anaesthesia and total hip replacement

Abstract: TOTAL HIP REPLACEMENT has become a frequent procedure since the initial work of Charnley, McKee, Watson, Ferrar and Ring in the early 1960s. The most popular technique, that of Miiller, ~ involves a socket prosthesis fixed in the acetabulum with acrylic bone cement. A femoral prosthesis is then fixed in the medullary cavity with the same acrylic cement. Peroperative complications associated with prosthesis implantation have ranged from transient hypotension, 8 cardiac arrest, 4 and embolic phenomena TM to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Received 20 January, acce@ted,for publication 4 February 1975 During total hip replacement in man, several investigations have revealed a transient reduction of arterial blood pressure, occurring mainly after the insertion of bone cement and insertion of the prosthesis into the femoral marrow cavity (PHILLIPS et al 1971, KIM & RITTER 1972, SOMMERLAD 1972, SCHUI~ et al 1973. Recently there have also been reports of depression of the arterial oxygen tension in connection with the implantation of cement and implantation of the prosthesis into the marrow cavity in man (PARK et al 1973, TURNBULL et al 1974. I n previous investigations these phenomena have been confirmed, and suggestions as to their causative mechanisms have been put forth (MODIG et al 1973a(MODIG et al , 1975.…”
mentioning
confidence: 97%
“…Received 20 January, acce@ted,for publication 4 February 1975 During total hip replacement in man, several investigations have revealed a transient reduction of arterial blood pressure, occurring mainly after the insertion of bone cement and insertion of the prosthesis into the femoral marrow cavity (PHILLIPS et al 1971, KIM & RITTER 1972, SOMMERLAD 1972, SCHUI~ et al 1973. Recently there have also been reports of depression of the arterial oxygen tension in connection with the implantation of cement and implantation of the prosthesis into the marrow cavity in man (PARK et al 1973, TURNBULL et al 1974. I n previous investigations these phenomena have been confirmed, and suggestions as to their causative mechanisms have been put forth (MODIG et al 1973a(MODIG et al , 1975.…”
mentioning
confidence: 97%
“…Several mechanisms have been proposed to account for this effect. [6][7][8] Epidural anaesthesia has been used safely for management of pheochromocytoma. 9-10 The technique permits a final assessment of sympathetic blockage prior to surgery.…”
mentioning
confidence: 99%
“…Other pulmonary complications that have also been reported are pulmonary capillary leaks (Safwat and Dror, 1982), an increased venous admixture (Tumbull et al, 1974;Modig and Molmberg, 1975;Modig, 1976), pulmonary hypertension, and elevated pulmonary vascular resistance (Modig and Molmberg, 1975;Rinecker, 1980). Contrary to previously reported pulmonary complications, Hughes et al (1972) reported no evidence of pulmonary dysfunction after THA with PMM in man.…”
Section: Cardiopulmonary Complicationsmentioning
confidence: 96%